Differentials in the Regional Operational Program expenditure for public services and infrastructure in the coastal cities of Sardinia (Italy) analyzed in the ruling context of the Regional Landscape Plan - Corrado Zoppi; Sabrina Lai (European Regional Science Association (ERSA), 2010)
The planning activity of the regional administration of Sardinia (Italy) is characterized by a deep change after the approval of the Regional Landscape Plan (RLP). The RLP, ruled by the National Code of Cultural Heritage and Landscape, establishes the directions for future Sardinian regional planning and requires that sectoral, province and city plans, and plans for protected areas, be changed to comply with its directions. The adjustment process could be conflictual, since cities, provinces, and bodies responsible for protected areas might disagree with the regional administration about the rules established by the RLP. These are particularly restrictive for coastal areas, where cities could suffer a sharp decline in building expansion rights and risk losing financial resources that would come from the impact fees paid by the developers. Moreover, payments of communal tax for real estate might decrease, since the value of land would plummet without development rights. The investment attraction capacity of Sardinian coastal cities could therefore drop as a consequence of the ruling framework of the RLP. The Sardinian regional operational program 2007-2013 concerning the European Regional Development Fund (ERDF) respects the rules of the ERDF on the investments for territorial cohesion (as defined by Regulation no. 1080/2006/EC), since it promotes their regional geographic concentration. With regards to Sardinian coastal cities, this paper analyzes the investment policies for public services and infrastructure implemented by the Sardinian Region through the Regional Operational Program, in order to assess the impact of the RLP. The first section develops a geographic information system (GIS) to define a territorial taxonomy of Sardinian coastal cities, by analyzing the spatial distribution of investment in public services and infrastructure and of other attributes concerning demography, urbanization, RLP ruling framework. The second section analyzes, through linear regression and logit methodologies, the investment policies concerning public services and infrastructure, and identifies correlations between the variables represented by the GIS. The methodological approach adopted in this paper can be used in regional planning processes to address the important issue of the often-conflictual relationship between the implementation of conservative planning policies and local economic development programs.
Keywords: 330